2001
DOI: 10.1191/096032701678227758
|View full text |Cite
|
Sign up to set email alerts
|

Taurine has a protective effect against thioacetamide-induced liver cirrhosis by decreasing oxidative stress

Abstract: Thioacetamide (TAA) administration (0.3 g/l of tap water for a period of 3 months) to rats resulted in hepatic cirrhosis as assessed by biochemical and histopathological findings. This treatment caused an increase in the levels of malondialdehyde (MDA) and diene conjugates (DCs) and a decrease in the levels of glutathione (GSH), vitamin E, vitamin C and the activities of glutathione peroxidase (GSH-Px) in the liver of rats. Superoxide dismutase (SOD) activities were unchanged. Taurine (2% w/w, added t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
64
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 26 publications
8
64
1
Order By: Relevance
“…4) Some investigators have demonstrated that taurine, when coadministered with ethanol, reduced ethanol-induced hepatic steatosis and lipid peroxidation. 5) Our recent studies have also shown that taurine treatment has a protective effect against thioacetamide-induced hepatic necrosis 6) and cirrhosis 7) by decreasing oxidative stress. Oxidative stress is known to play an important role in the pathogenesis of ethanol-induced liver injury.…”
mentioning
confidence: 94%
“…4) Some investigators have demonstrated that taurine, when coadministered with ethanol, reduced ethanol-induced hepatic steatosis and lipid peroxidation. 5) Our recent studies have also shown that taurine treatment has a protective effect against thioacetamide-induced hepatic necrosis 6) and cirrhosis 7) by decreasing oxidative stress. Oxidative stress is known to play an important role in the pathogenesis of ethanol-induced liver injury.…”
mentioning
confidence: 94%
“…It is therefore possible that another mechanism besides the improving eŠect on the serum lipoprotein level may play an important role in the decreasing or preventive eŠect of taurine on atherosclerosis. In our previous studies, we have demonstrated that a taurine treatment had a protective eŠect against thioacetamide-induced hepatic necrosis 6) and cirrhosis 7) by decreasing oxidative stress. Clinical and experimental studies have shown that oxidative stress and lipid peroxidation are involved in the pathogenesis of atherosclerosis.…”
mentioning
confidence: 95%
“…1) Some investigators have suggested that taurine has hypolipidemic, 2,3) antiatherosclerotic [4][5][6] and hepatoprotective effects. [7][8][9] Although the mechanism for these effects of taurine is not clear, the effects may be related to its hypolipidemic and/or antioxidative effect. 1,6) We have recently reported that taurine ameliorated cholesterol accumulation and cholesterol-induced oxidative stress in the plasma, liver, and aorta of rabbits fed on a high-cholesterol (HC) diet, and that this may have been related to its antioxidative effect, besides the reducing effect on serum lipids in this study.…”
mentioning
confidence: 99%